Persistent and Permanent Point of Views of Two Stages DNA Splicing Languages - Mudaber, Mohammad Hassan; Yuhani, Yusof; Mohd Sham, Mohamad; Wen, Li Lim (International Science Congress Association, 2015)
Yusof-Goode (Y-G) splicing system was formulated by Yusof in 2012 to present the existence relation between formal language theory and molecular biology in a convenient approach. In terms of biology, the recombinant deoxyribonucleic acid (DNA) molecules can often be split with the existence of actual restriction enzymes. For this property of the recombinant DNA strands is called persistent. Therefore, determining the persistency of the hybrid templets of DNA strands, after acting restriction enzymes on the initial DNA strands, by providing mathematical proof is considered as a new contribution in the areas of DNA molecular. In this work, the persistent and permanent aspects of two stages splicing languages are investigated and discussed via Y-G approach. This investigation focuses on number of cutting sites in initial strings as well as sequences factors of splicing rules. Accordingly, the persistency and permanency of the above splicing languages with respect to two initial strings (with two cutting sites) and two rulesare presented as lemmas, theorems, and corollaries. Nevertheless, an example is provided, which shows the real meaning of theorem in terms of biology.